Pengaruh Celebrity Endorser dan Kualitas Produk terhadap Keputusan Pembelian Produk Obat Jerawat Merek Acnes di Kota Singaraja - Ni Kadek Dani Maryanti (Jurnal Manajemen Perhotelan dan Pariwisata, 2022)
This study intended to examine the effect partially and simultaneously of celebrity endorsers and product quality on the purchase decision for acne medication of Acnes brand in Singaraja City. This study uses a causal quantitative design, where consumers who use acne medications of Acnes brand in Singaraja are the subject of this research. The sample collection technique uses in this research is purposive sampling and the number of samples used in this research was 120 respondents. The data was collected using a questionnaire method and then analysis technique used was multiple linear regression analysis. The results of this research are: (1) celebrity endorser and product quality together have a significant influence on the purchase decision for acne medication of Acnes brand in Singaraja City. (2) celebrity endorser has a positive and significant effect on the purchase decision for acne medication of Acnes brand in Singaraja City. (3) product quality has a positive and significant effect on the purchase decision for acne medication of Acnes brand in Singaraja City